Adsorption of heavy metals from mine wastewater using amino-acid modified Montmorillonite. Issue 1 (31st December 2023) - Boahen, Christiana; Wiafe, Samuel; Owusu, Fredrick; Bian, Liang
ABSTRACT: This study was conducted to identify the ability of a modern developed amino-acid modified montmorillonite clay (AA-Mont) to adsorb Cu 2+, Pb 2+ and Ni 2+ cations from a multi-aqueous wastewater. This experimental was conducted to identify the potential of clay-based adsorbents to remediate pollutants from the PRA river basin. Experimental wastewater was prepared using a range of the lowest and highest recorded upstream and downstream heavy metal concentrations of u 2+ (10.84 mg/L-108.48 mg/g), Ni 2+ (7.99 mg/g–79.92 mg/g), and Pb 2+ (33.538 mg/L—335.38 mg/L). The variants of the designed clay-based adsorbents were L-Cysteine montmorillonites (Cys-Mont), Glycine montmorillonite (Gly-Mont), and L-lysine Montmorillonites (Lys-Mont) prepared at pH 4, 5, and 6 respectively. The experimental conditions were; Adsorbent dosages range = 25 mg–400 mg, pH = 6.0, Contact time = 24 hrs, Temperature = 25°C and Shaker speed = 180 rmp. After the adsorption experiments, it was identified that the maximum average removal efficiency obtained for Cu 2+, Ni 2+, and Pb 2+ were all attained at adsorbent dosage 400 mg/L and in the order Lys-Mont (99.82%)>Cys-Mont (99.28%)>Gly-Mont (95.8%). Thus, the modified Lys-Mont clay exhibited the highest heavy metal adsorption capacity amongst the above three studied. The highest and lowest adsorbed metal pollutants amounts recorded for Lys-Mont were Cu 2+ (86.49 and 8.65) mg/g, Ni 2+ (44.51 and 5.99) mg/g, and Pb 2+ (267.85 and 26.67) mg/g respectively. The number of metal ions adsorbed per unit mass for each metal cation tested decreased with increasing adsorbent dosage. The general order of selectivity documented for all the AA-Monts in this study was Pb>Cu>Ni which is similar to the levels in the prepared wastewater solution (Pb>Cu>Ni). The findings of this study have shown that heavy metal polluted river basins can remediated given the right conditions of temperature, adsorbent dosage, pH and agitation speed. Graphical abstract: uf0001